Influence of short-duration densification on the temperature profile of cross-laminated timber during an open burning test - Charles Michael Albert; Liew, Kang Chiang (the Korean Society of Wood Science and Technology, 2025)
This study investigated the fire performance of cross-laminated timber (CLT) manufactured from the densified laminas of Paraserianthes falcataria, a fast-growing timber species. The aim of the study was to provide insights into the influence of short-duration densification on the thermal behavior of CLT during open burning, where compression ratios (40%, 50%, 60%) were applied. The outcomes indicated that higher compression ratios resulted in the formation of an insulating char layer that delayed the charring rate and enhanced the fire resistance of CLT. Notably, a 50% compression ratio was found to be optimal to achieve the desirable charring rate. The study further investigated the temperature-profile dynamics, emphasizing the impact of densification on the dynamic temperature changes in the CLT during a fire. The findings also highlighted the influence of the adhesive characteristics on the charring rate and temperature dynamics of the CLT, contributing to a deeper understanding of ways to produce CLT with desirable Physico mechanical properties and excellent structural integrity